Magnetic molecularly imprinted polymer nanoparticles for the extraction and clean-up of thiamethoxam and thiacloprid in light and dark honey - Abdulhussein, Ahmed Qasim (Elsevier, 2021)
In this work, new selective and sensitive dual-template molecularly imprinted polymer nanoparticles (MIPs) were synthesized and characterized. Sorbent MIPs were investigated for simultaneous extraction and clean-up of thiamethoxam and thiacloprid from light and dark honey samples. In this study, ultra-high-performance liquid chromatography–tandem mass spectrometry triple-quadrupole (UHPLC-MS/MS) (QQQ) was used to detect and quantify the pesticides. The kinetic model with adsorption kinetics of sorbent was investigated. The optimal adsorption conditions were 80 mg of polymer MIPs, a 30-min extraction time, and a pH of 7. The detection limit (LOD) and the quantification limit (LOQ) varied from 0.045 to 0.070 µg kg−1 and from 0.07 to 0.10 µg kg−1, respectively. The intra-day and inter-day precision (RSD, %) ranged from 1.3 to 2.0% and from 8.2 to 12.0%, respectively. The recovery of thiamethoxam and thiacloprid ranged from 96.8 to 106.5% and 95.3 to 104.4%, respectively, in light and dark honey samples. © 2021 Elsevier Ltd